2013
DOI: 10.1007/s10803-013-1836-5
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory Speech Perception in Children with Autism Spectrum Disorders

Abstract: This study examined unisensory and multisensory speech perception in 8–17 year old children with autism spectrum disorders (ASD) and typically developing controls matched on chronological age, sex, and IQ. Consonant– vowel syllables were presented in visual only, auditory only, matched audio-visual, and mismatched audiovisual (“McGurk”) conditions. Participants with ASD displayed deficits in visual only and matched audiovisual speech perception. Additionally, children with ASD reported a visual influence on he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
155
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 134 publications
(168 citation statements)
references
References 45 publications
8
155
2
Order By: Relevance
“…Various researchers have determined that there does exist an extended temporal binding window in ASD, meaning that individuals with ASD continue to integrate sensory information over a larger gap in time than do TD individuals (Foss-Feig et al 2010;Kwakye et al 2011;Woynaroski et al 2013). The current results indicating that the ASD group had significantly lower accuracy than the TD group on the 2F1B (i.e., fusion illusion) and 2F0B trials may be explained by the presence of an expanded temporal binding window.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…Various researchers have determined that there does exist an extended temporal binding window in ASD, meaning that individuals with ASD continue to integrate sensory information over a larger gap in time than do TD individuals (Foss-Feig et al 2010;Kwakye et al 2011;Woynaroski et al 2013). The current results indicating that the ASD group had significantly lower accuracy than the TD group on the 2F1B (i.e., fusion illusion) and 2F0B trials may be explained by the presence of an expanded temporal binding window.…”
Section: Discussionmentioning
confidence: 47%
“…The McGurk effect (i.e., illusory auditory perception influenced by discordant visual information) has been one frontrunner paradigm for studying MSI in TD individuals as well as in ASD (Foxe and Molholm 2009;Iarocci and McDonald 2006). While some studies have identified a diminished McGurk effect in ASD (Bebko et al 2014;Mongillo et al 2008;Williams et al 2004), others have found that the effect is contingent on developmental factors (Taylor et al 2010), socio-communicative impairments (Iarocci et al 2010, or task-related temporal factors (Woynaroski et al 2013).The speech-in-noise paradigm, which is based on the facilitatory effect of multisensory stimulation, has also been used to better understand multisensory integration processes in typical development as well as in ASD. Using the speech-in noise approach to compare adolescents with Abstract Previous studies have suggested audiovisual multisensory integration (MSI) may be atypical in Autism Spectrum Disorder (ASD).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is currently some debate in the literature about differences in multisensory integration as indexed by McGurk perception. Some groups have found that TD subjects have increased McGurk perception compared with ASD subjects 27,36 , while others have found that ASD subjects had higher McGurk perception 37 . Some of these discrepancies may be explained by differences in the McGurk stimulus used in each study.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Along with its utility in characterizing multisensory temporal function in "neurotypical" populations across the lifespan, elements of the described task battery have been used to assess sensory and multisensory processes in individuals with ASD [26][27][28]37 . Although sensory disturbances have been classically associated with autism, it is only recently that these disturbances have entered the diagnostic vernacular, and that a stronger appreciation of how altered multisensory function may contribute to the autism phenotype has been gained.…”
Section: Discussionmentioning
confidence: 99%